2012
DOI: 10.1002/jor.22292
|View full text |Cite
|
Sign up to set email alerts
|

Repeated subrupture overload causes progression of nanoscaled discrete plasticity damage in tendon collagen fibrils

Abstract: A critical feature of tendons and ligaments is their ability to resist rupture when overloaded, resulting in strains or sprains instead of ruptures. To treat these injuries more effectively, it is necessary to understand how overload affects the primary load-bearing elements of these tissues: collagen fibrils. We have investigated how repeated subrupture overload alters the collagen of tendons at the nanoscale. Using scanning electron microscopy to examine fibril morphology and hydrothermal isometric tension t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
81
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 67 publications
(94 citation statements)
references
References 19 publications
9
81
4
Order By: Relevance
“…For the fibres extracted from overloaded tendons, the observed decrease in refractive index contrast can be similarly explained. Previous work has shown that the repeated overload regime used here causes collagen fibrils to enlarge as their periphery undergoes molecular denaturation [11]. In addition to changes in water content, collagen denaturation -uncoiling of the collagen molecule's native triple-helix -may have also contributed to the changes in refractive index contrast observed in the present study with heat treatment and mechanical overload.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…For the fibres extracted from overloaded tendons, the observed decrease in refractive index contrast can be similarly explained. Previous work has shown that the repeated overload regime used here causes collagen fibrils to enlarge as their periphery undergoes molecular denaturation [11]. In addition to changes in water content, collagen denaturation -uncoiling of the collagen molecule's native triple-helix -may have also contributed to the changes in refractive index contrast observed in the present study with heat treatment and mechanical overload.…”
Section: Discussionmentioning
confidence: 64%
“…The other tendon reached a maximum stress of 51.0 MPa at a strain of 18.9%. As expected from previous experiments [11,13], progressively smaller maximum stresses, and larger maximum strains were recorded during the subsequent four overload cycles. Tensile overload did not affect fibre diameter, but significantly reduced refractive index contrast, causing a mean decrease of 21% relative to the control samples (Figure 4).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Although the specific structural mechanisms leading to failure were not investigated in the current study, Veres and colleagues have suggested that repeated subrupture loading results in fibril denaturation events that form progressive fibril kinks and the accumulation of damage in bovine tail tendons (Veres et al, 2013; Veres and Lee, 2012). Such changes have been shown to primarily occur early during repeated loading (Veres et al, 2013), which was also observed in the current study. In addition, our laboratory has recently developed a novel method to investigate crimp during mechanical testing (Buckley et al, 2013a), which could be another imaged-based metric for subrupture damage accumulation.…”
Section: Discussionmentioning
confidence: 94%
“…Several studies have used fatigue loading to induce damage in tissue (Fung et al, 2010; Fung et al, 2009; Sereysky et al, 2012; Wren et al, 2003), investigate theoretical endurance limits in tendon (Schechtman and Bader, 1997, 2002; Wang et al, 1995), quantify subsequent biological changes (Andarawis-Puri et al, 2012a; Andarawis-Puri et al, 2012b; Legerlotz et al, 2011), and identify potential causes of failure (Veres et al, 2013; Veres and Lee, 2012). Although the specific structural mechanisms leading to failure were not investigated in the current study, Veres and colleagues have suggested that repeated subrupture loading results in fibril denaturation events that form progressive fibril kinks and the accumulation of damage in bovine tail tendons (Veres et al, 2013; Veres and Lee, 2012).…”
Section: Discussionmentioning
confidence: 99%